Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Factors Affecting Acceptance of Teachers in Schools in North of Jeddah to Use Virtual Classrooms in Light of the Unified Theory of Acceptance and Use of Technology (UTAUT)Co-Prof. Leena Ahmad Alfarani, Mrs. Bayan Khalid Almoalim , Mrs. Ohood Obiedullah Albeladi2. The Misconceptions in Science among Students of the Faculty of Science at Palestine Technical University KadoorieCo-Prof. Nuha Ismail Iter3. Factors for the tenth-grade students' reluctance to interact in the classroom during distance learning(An exploratory study from the point of view of students in the Sultanate of Oman)Mr. Said Mohammed Alkalbani4. The Islamic rooting of causes and methods managing organizational conflictMrs. Dalal Dabes Mohammed Aldaadi5. Brain Dominance and its relationship to Tolerance for Cognitive Ambiguity and Academic Achievement among gifted and normally developing secondary stage female students in Makkah Al-MukarramahMrs. Elham Majhoud Alzahrani6. Teachers' awareness of behavioural problems and mechanisms for dealing with them for early childhood(Study from kindergarten teachers' destination in Hafar Al-Batin governorate)Mrs. Hana Mohammed S. Alaniz7. The mental health of the hearing impaired in Jeddah during the CoronavirusMrs. Norah Dakhilallah Alsubaie, Dr. Manal Yahia Baamer8. The Effectiveness of Online Counselling Program Based on the Acceptance and Commitment to Improve Post-Traumatic Growth among Females Recovered from Corona Virus Disease (Covid-19): An Experimental study in JeddahDr. Hanan Hamed Al-Sofyani, Prof. Yahya Abdallah Al-Rfei
Keywords: Journal of Educational and Psychological Sciences